Risk factors of ectopic pregnancy: a study in a tertiary care centre - Neelima, Beera; Vanamala, V. G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Over the years, there has been a considerable rise in the incidence of ectopic pregnancy. This study was undertaken to identify the risk factors that contribute to this condition, so that immediate action can be taken so as to save the mother. Methods: 62 women, in their first trimester of pregnancy who were diagnosed with ectopic pregnancy were included in the study. Demographic details, clinical and obstetric details were taken from all the patients. Ultrasound was performed to confirm the ectopic pregnancy. Results: Out of the 62 patients, most of them with ectopic pregnancy were found to be in the 26-30 (40.3%) year’s age group. Smoking, whether active or passive was observed in nearly 42% of the cases. The mean gravid status among the women was 3, with 34 live births. 21 of them had induced abortions and 4 were spontaneous. PID was observed in 12 patients (19.4%), 17.7% were IUD users. Conclusions: Risk factors such as previous ectopic pregnancy, use of contraceptives, infertility, PID, abortion as well as increased maternal age aid in the early detection of ectopic pregnancy in women resulting in proper and timely treatment.